The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1051/kmae/2012020
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofLernaea cyprinaceaLinnaeus 1758 (Crustacea : Copepoda) almost a decade after an initial parasitic outbreak in fish of Malilangwe Reservoir, Zimbabwe

Abstract: Key-words:Lernaea cyprinacea, Clinostomoides brieni, parasite, cichlids, intensity, MalilangweAn assessment was carried out on the impact of Lernaea cyprinacea on fish populations ten years after its first outbreak in the Malilangwe reservoir, and Lernaea cyprinacea is currently showing no sign of declining in the reservoir. Eight fish species were examined for ectoparasite prevalence and intensity. The possible relationship between L. cyprinacea infestation and environmental factors were investigated. Two par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Although occurring sympatrically with infected fishes, gobioid fishes were often not infested by L. cyprinacea (e.g. Kritscher, 1975;Kvach, 2004;Dalu et al, 2012;Krasnovyd et al, 2012;Kvach et al, 2014Kvach et al, , 2015Zhokhov et al, 2017) (Tab. S1).…”
Section: Discussionmentioning
confidence: 99%
“…Although occurring sympatrically with infected fishes, gobioid fishes were often not infested by L. cyprinacea (e.g. Kritscher, 1975;Kvach, 2004;Dalu et al, 2012;Krasnovyd et al, 2012;Kvach et al, 2014Kvach et al, , 2015Zhokhov et al, 2017) (Tab. S1).…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first record of infection by L. cyprinacea (68.1%) in this sample of guppy fish examined from KSA. Although L. cyprinacea seems to have a random choice for attachment on the body host, it was shown that the parasites were fixed especially on the fins and skin [29] . The same observations were previously reported in many other literatures [30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Plaul et al (2010) noted that prevalence and intensity of infection reduce with decreases in water temperature. However, Dalu et al (2012) observed that parasite intensity can be negatively correlated with water temperature in tropical areas. Because the optimum temperature for the anchor worm is between 23°C and 30°C (Plaul et al, 2010), the negative relationship observed by Dalu et al (2012) may be related to parasite thermal tolerances, as water temperature exceeded the tolerance thresholds (mean values from 19.3°C to 30.1°C in July and March, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, Dalu et al (2012) observed that parasite intensity can be negatively correlated with water temperature in tropical areas. Because the optimum temperature for the anchor worm is between 23°C and 30°C (Plaul et al, 2010), the negative relationship observed by Dalu et al (2012) may be related to parasite thermal tolerances, as water temperature exceeded the tolerance thresholds (mean values from 19.3°C to 30.1°C in July and March, respectively). This study is in agreement with the abovementioned studies supporting the hypothesis that high water temperatures within parasite thermal tolerances can increase infestation levels and consecutively promote host-parasite interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation